Dental caries experience and its relationship to social and behavioural factors among 3–5-year-old children in Uganda - S. N. KIWANUKA, A. N. ÅSTRØM, & T. A. TROVIK (Paediatric Dentistry, 2004)
The aim of this study was to assess the socio-demographic and behavioural correlates of caries experience and sugar intake patterns among pre-school children in Uganda.